Pengaruh Gaya Kepemimpinan dan Pelatihan Kerja terhadap Kinerja Karyawan CV. Wahyu Artha Technic - Wahyu Haditama; Dovina Navanti; Dewi Sri Wulandari (Journal of Islamic Economics and Finance, 2024)
Human Resources (HR) is a crucial asset for every organization, including CV Wahyu Artha Technic. Effective HR management through good leadership and proper training is essential to achieve company goals. This study aims to explore the relationship between leadership style and job training on employee performance at CV. Wahyu Artha Technic, West Java. Data were obtained through questionnaires completed by 65 respondents in May 2024, with a 100% response rate. The results showed that participative leadership style and timely job training have a positive and significant influence on employee performance. Sales data shows fluctuations from year to year, which is closely related to the lack of training and ineffective leadership style. A survey of respondents showed that employee performance can be improved through opportunities provided by leadership to convey feedback and complaints. Training that is relevant to operational needs and technological developments is proven to improve employee competence and productivity. The conclusion of this study is that good leadership style and structured job training significantly improve employee performance at CV. Wahyu Artha Technic. The recommendations of this study include the importance of effective communication between management and employees as well as the development of continuous training programs to maintain employee competence and motivation. Implementation of these strategies is expected to optimize overall organizational performance.